SAT0435 Undiagnosed Connective Tissue Diseases in Pulmonary Arterial Hypertension Patients: Baseline and Follow-Up Results from a PAH Referral Centre. (9th June 2015) - Codullo, V.; Cavagna, L.; Ghio, S.; Scirè, C.A.; Guzzafame, E.; Scelsi, L.; Rossi, S.; Montecucco, C.; Caporali, R.
Abstract : Background: Among different subgroups of pulmonary arterial hypertension (PAH), those associated with connective tissue diseases (CTDs) are a specific entity with distinct hemodynamic and prognostic features. PAH screening is routinely performed in systemic sclerosis (SSc) and in other CTDs. Conversely, as suggested by international guidelines, it is important to rule out CTDs in patients with PAH, because patients diagnosed as idiopathic PAH (iPAH) may have an associated CTD previously unrecognized. Despite this assumption, no data about this phenomenon have been reported yet. Objectives: To analyse frequency and prognosis of undiagnosed CTDs in PAH patients Methods: Fifty consecutive patients with PAH confirmed by right heart catheterization referred at the Cardiology Division of our University Hospital without a previous CTD diagnosis, rheumatology assessment or the occurrence of known conditions explaining PAH were evaluated for the frequency of any CTD. Patients underwent complete clinical, laboratory and instrumental evaluation including capillaroscopy and antinuclear antibody (ANA) determination. Current classification criteria were used for the identification of CTD. These patients were subsequently followed-up and their survival has been reported. Statistical analysis was performed using STATA v11. Results: Of the 49 patients enrolled (1 patients refused rheumatology assessment), 17 were classified as CTD-PAH (12 SSc, 2 SLE, 2 undifferentiated CTD, 1 Sjögren Syndrome), corresponding to an estimated prevalence (95%CI) of 34.7% (21.7-49.6%). ANA positivity was associated with a sensitivity of 94% (95%CI 71.3-99.9%) and a specificity of 78.1% (60-90.7%) for a diagnosis of CTD-PAH; Raynaud's phenomenon (RP) was associated with a sensitivity of 83.3% (95%CI 51.6-97.9%) and a specificity of 100% (90.5-100%) for a diagnosis of SSc-associated-PAH. At PAH diagnosis, SSc patients were older and had a lower creatinine clearance with respect to both iPAH and other CTD-PAH. Brain Natriuretic Peptide levels were lower in other-CTDs than in SSc and iPAH. NYHA functional class, mean Pulmonary Arterial Pressure (mPAP), cardiac index and pulmonary vascular resistance did not differ between groups. An inverse linear relationship between mPAP and cardiac index was observed in the CTD group. After a median follow-up of 44 (2-132) months, 18/49 (36.7%) patients were deceased: 10/32 (31.2%) in the iPAH group, 1/5 (20%) in the CTD and 7/12 (58.3%) in the SSc-PAH group. Mortality was significantly higher in SSc-PAH (HR 3.07, 1.02-9.23, p<0.05) versus iPAH whilst there was no statistically significant difference between non SSc CTDs and iPAH (Figure 1 ). Conclusions: Our results showed a high prevalence of undiagnosed CTDs, particularly SSc, in patients with iPAH without a previous rheumatological assessment. All patients with RP in our series were diagnosed with SSc. The reported prevalence of RP in iPAH in the literature ranges from 5 to 30% and this might be accounted by the high prevalence of an undiagnosed rheumatic disease in these cohorts. Our data stress the importance of a rheumatological assessment in PAH, especially because of the unfavourable prognostic impact of an associated SSc in these patients. Disclosure of Interest: None declared